2019
DOI: 10.1111/cas.14254
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of capmatinib in MET‐positive solid tumor patients: Dose escalation and expansion of selected cohorts

Abstract: Capmatinib is an oral, ATP-competitive, and highly potent, type 1b MET inhibitor.Herein, we report phase 1 dose-escalation results for capmatinib in advanced METpositive solid tumor patients and dose expansion in advanced non-lung tumors.Capmatinib was well tolerated with a manageable safety profile across all explored doses. Dose-limiting toxicities (DLT) occurred at 200 mg twice daily (bid), 250 mg bid, and 450 mg bid capsules; however, no DLT were reported at 600 mg bid (capsules).Capmatinib tablets at 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…Interestingly, very-high MET mRNA expression closely correlated with MET gene amplification by NGS or FISH and was mutually exclusive with METΔex14. Therefore, it is not surprising that the phenotype of the patients with very-high MET mRNA agrees with the characteristics previously reported in patients with high MET amplification (defined as FISH gene copy number, GCN≥6 or ≥10) [16,17,39,40].…”
Section: Accepted Articlesupporting
confidence: 86%
“…Interestingly, very-high MET mRNA expression closely correlated with MET gene amplification by NGS or FISH and was mutually exclusive with METΔex14. Therefore, it is not surprising that the phenotype of the patients with very-high MET mRNA agrees with the characteristics previously reported in patients with high MET amplification (defined as FISH gene copy number, GCN≥6 or ≥10) [16,17,39,40].…”
Section: Accepted Articlesupporting
confidence: 86%
“…23 Tivantinib has been previously studied in NSCLC patients, and was discontinued due to futility in an interim analysis; 24 , n = 38) demonstrated clinical safety and determined the dose to be safe was 400 mg b.i.d. 31,32 Preliminary anti-tumor efficacy was reported in NCT01324479 and NCT02276027 in MET altered tumors. 33,34 Capmatinib efficacy in METex14 NSCLC was established in the GEOMETRY mono-1 trial (NCT02414139), a multicenter, non-randomized, open-label, multicohort, and phase II study enrolling 97 metastatic METex14 NSCLC patients.…”
Section: Clinicopathologic Characteristics Of Metex14 Splicing Alteramentioning
confidence: 99%
“…11,12 Phase I and Phase II studies have shown a manageable safety and robust efficacy profile of capmatinib, both as monotherapy and in combination with other anticancer therapies, in patients with solid tumours. [13][14][15][16][17][18][19][20] The therapeutic dose of capmatinib is 400 mg twice daily. In clinical trials, patient populations are selected with limited or no comorbidities and concurrent medications are not permitted, follow-up period is much narrower, and the toxicities are detected earlier, so patient populations enrolled may not accurately represent the general oncology population.…”
Section: Introductionmentioning
confidence: 99%